Pengaruh Kualitas Produk, Online Customer Review, dan Online Customer Rating Terhadap Keputusan Pembelian Dengan Kepercayaan Konsumen Sebagai Variabel Mediasi - Intan Nur Rahmawati (Jurnal Impresi Indonesia, 2025)
This study aims to analyze the influence of product quality, online customer review, and online customer rating on purchasing decisions, with consumer trust as a mediating variable among TikTok Shop users in Purwokerto. A quantitative approach was employed using a survey method distributed to 100 respondents. The results indicate that product quality and online customer review significantly affect consumer trust, while online customer rating does not. Consumer trust has a positive effect on purchasing decisions and mediates the relationship between product quality and online customer review with purchasing decisions. These findings highlight the importance for businesses to foster consumer trust through improved product quality and positive customer reviews on digital platforms.